Fate of the Lhapa - Sifers, Sarah (United States, 2007)
Verzio FF submission Fate of the Lhapa is a feature-length documentary about the last three Tibetan shamans (lhapas) living in a Tibetan refugee camp in Nepal. With no other descendants to carry on their healing practices and a younger generation attending schools, acculturating, and modernizing, these "sucking doctors" are practicing an endangered tradition. Each lhapa requested that their story be filmed so that an historical record would be created. Their fear was that the next heir might not appear until after the old men's deaths. Subsequently, with no lhapa alive to mentor the children, the documentary would be used to transmit the knowledge to the next generation. These tales of nomadic childhoods, shamanic callings and apprenticeships, cosmologies of disease and treatments, and of their flight from Tibet during the Chinese occupation in the late 1950s will be juxtaposed with images of present-day life in the camp, current healing practices and shared concerns of the future and the fate of their tradition. This is a touching portrayal of life in exile in a refugee camp in Nepal.